Sosialisasi Penanganan Kesehatan pada Ternak Kambing di Desa Sungai Langka, Kabupaten Pesawaran, Lampung - Agung Adi Candra; Dwi Desmiyeni Putri; Riko Noviadi; Nani Irwani; Heni Suryani; Gusma Gama Maradon; Zairiful Zairiful; Harfina Rais; Desi Maria Sinaga (Jurnal Pengabdian Masyarakat (ABDIRA), 2023)
This activity aims to provide education to farmers in Sungai Langka Village, Pesawaran Regency regarding health care for ruminants. The main target of this activity is the etawa breeder in Sungai Langka Village. The activity method is carried out in monologue and practice. The activity began with presentation, how to identify symptoms of livestock diseases and how to handle it. Based on the results of the activities that have been carried out, farmers are very enthusiastic about the socialization material provided. This was proven by the active role of the participants, especially farmers, in the discussion session regarding how to handle livestock health which is commonly found in PE goats. After socialization are held, farmers gain knowledge about how to handle common diseases and able to apply disease control in the field. The results of this activity are expected to minimize the number of livestock deaths due to disease and the number of livestock affected by the disease can be handled properly. Decreasing diseases will contribute to increasing the productivity of ruminants, especially PE goats in Sungai Langka Village.